Contribution of Government Policy Stakeholders in Improving the Quality of Education in Indonesia - Andri Gunawan; Nur Rohim Yunus; Faiqatul Husna (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This article seeks to investigate Indonesian government policymakers' role in enhancing education quality. This study employed a qualitative approach focusing on the literature and the Law. Data is gathered from various sources, including scientific journals, government publications, and educational policy documents. The findings of this study indicate that government policymakers play a crucial role in the development and enhancement of the education system in Indonesia. The Government creates a high-quality, inclusive, and competitive educational environment through various programs, policies, and budget allocations. The formulation of the appropriate procedure is crucial to attaining the objective of improving the quality of education. Education policies that are comprehensive and in line with the community's requirements are the foundation for sustainable education development. In addition, rigorous monitoring and evaluation by government stakeholders contribute to implementing effective policies and following national education standards. Improving the caliber of the teaching staff is also a key objective, necessitating ongoing training and professional development. Improving education quality also depends on the Government's dedication to allocating the education budget. By allocating sufficient funds, the Government can construct and maintain an appropriate educational infrastructure, offer tuition assistance, and promote increased access to education for all segments of society.Keywords: Contribution; Government Policy Holders; Education quality; Education system; Indonesia Abstrak:Artikel ini berusaha menyelidiki peran pembuat kebijakan pemerintah Indonesia dalam meningkatkan kualitas pendidikan. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan fokus pada literatur dan hukum. Data dikumpulkan dari berbagai sumber, termasuk jurnal ilmiah, publikasi pemerintah, dan dokumen kebijakan yang berkaitan dengan pendidikan. Temuan penelitian ini menunjukkan bahwa pembuat kebijakan pemerintah memainkan peran penting dalam pengembangan dan peningkatan sistem pendidikan di Indonesia. Pemerintah berkontribusi dalam menciptakan lingkungan pendidikan yang berkualitas, inklusif, dan berdaya saing melalui berbagai program, kebijakan, dan alokasi anggaran. Perumusan kebijakan yang tepat sangat penting untuk mencapai tujuan peningkatan mutu pendidikan. Kebijakan pendidikan yang komprehensif dan sesuai dengan kebutuhan masyarakat merupakan landasan pembangunan pendidikan yang berkelanjutan. Selain itu, pemantauan dan evaluasi yang ketat oleh pemangku kepentingan pemerintah berkontribusi pada implementasi kebijakan yang efektif dan sesuai dengan standar nasional pendidikan. Meningkatkan kualitas staf pengajar juga merupakan tujuan utama, yang memerlukan pelatihan berkelanjutan dan pengembangan profesional. Peningkatan mutu pendidikan juga tergantung pada kesungguhan pemerintah dalam mengalokasikan anggaran pendidikan. Dengan mengalokasikan dana yang cukup, pemerintah dapat membangun dan memelihara infrastruktur pendidikan yang memadai, menawarkan bantuan biaya pendidikan, dan mendorong peningkatan akses pendidikan bagi semua lapisan masyarakat.Kata kunci: Kontribusi; Pemangku Kebijakan Pemerintahan; Kualitas Pendidikan; Sistem Pendidikan; Indonesia